How innovation affects performance - Ksenia Gonchar; Maria Kristalova (Friedrich Schiller University Jena, 2019)
This paper studies how innovation strategies of Russian manufacturing firms affect various features of firm performance. A multi stage model is used, which relates the firm's decision to undertake R&D to its innovation output, technical efficiency, labor productivity, and growth. We also include imports into the knowledge production function, because catching up economies may adopt technologies embodied in imported hardware. Additionally, we link productivity and innovation output to survival. We find that both types of knowledge input - R&D and imports - strongly determine innovation. Innovations yield the strongest performance return in the case of catching up to technological frontier. Product innovation is more beneficial than process innovation in all performance features except for labor productivity. However, higher efficiency does not improve the growth rates or survival time of manufacturing firms. Taken together, these results show that innovation is not uniformly rewarded across all features of firm performance.
Keywords: C30; D24; O30; 330; innovation; productivity; growth; survival; Russia